If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7y + 6 = 8y + 7 Reorder the terms: 6 + 7y = 8y + 7 Reorder the terms: 6 + 7y = 7 + 8y Solving 6 + 7y = 7 + 8y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-8y' to each side of the equation. 6 + 7y + -8y = 7 + 8y + -8y Combine like terms: 7y + -8y = -1y 6 + -1y = 7 + 8y + -8y Combine like terms: 8y + -8y = 0 6 + -1y = 7 + 0 6 + -1y = 7 Add '-6' to each side of the equation. 6 + -6 + -1y = 7 + -6 Combine like terms: 6 + -6 = 0 0 + -1y = 7 + -6 -1y = 7 + -6 Combine like terms: 7 + -6 = 1 -1y = 1 Divide each side by '-1'. y = -1 Simplifying y = -1
| 6x+3(x-20)=62-(x+20) | | (4)6-(5/8) | | (x^2+7)+y^2=9 | | (x^2+7)+y^2=7 | | (2x-5)dx+(4x-y)dy=0 | | 29+x=1.5x | | 9u+9=3(u+5) | | 51=7(-1+2v)2 | | cos(68)=x/10.3 | | 8x^2+14-22= | | 5x+2(2x+5)=37 | | 294b^2-150= | | 105b^2+10ab-24a^2b= | | x^2+20x-12000=0 | | x-(-3x+8)=4 | | 15/3-4i | | 100x=15 | | 5(x-17)=-2(x+14) | | 10x-x=14 | | 100x-10x=108 | | 100x-10x=11 | | 7a+23=3 | | x(5x^2+10x-15)=0 | | y=px+a | | y=px | | 0=6x^2+10x-16 | | 6(5x+2)=36x+10-2(3x-6) | | 13-3y+3y=15 | | 4(x)2=100 | | 16x+11y=120 | | (1-7z)(5)= | | (x+0.34)(x+.23)=2 |